Association between type 1 diabetes and female sexual dysfunction - Virginia Zamponi; Rossella Mazzilli; Olimpia Bitterman; Soraya Olana; Cristina Iorio; Camilla Festa; Chiara Giuliani; Fernando Mazzilli; Angela Napoli (BMC, 2020)
Abstract Background This study aims to evaluate: 1) the prevalence of Female Sexual Dysfunction (FSD) in women affected by type 1 Diabetes Mellitus (DM) and the control group; 2) the correlation between duration of DM, HbA1C levels and sexual life quality; 3) the relationship between different methods of insulin administration and sexual life quality; 4) the correlation between FSD and diabetes complications. Methods We selected 33 women with type 1 DM and 39 healthy women as controls. Each participant underwent a detailed medical history and physical examination and completed the 6-item Female Sexual Function Index questionnaire (FSFI-6). In patients affected by type 1 DM, the different methods of insulin administration (Multi Drug Injection - MDI or Continuous Subcutaneous Insulin Infusion - CSII) and the presence of DM complications were also investigated. Results The prevalence of FSD (total score ≤ 19) was significantly higher in the type 1 DM group than in the control group (12/33, 36.4% and 2/39, 5.2%, respectively; p = 0.010). No statistically significant differences were found regarding FSD according to the presence of complications, method of insulin administration or previous pregnancies. Conclusions This study underlined that FSD is higher in women affected by type 1 DM than in healthy controls. This could be due to the diabetic neuropathy/angiopathy and the type of insulin administration. Therefore, it is important to investigate FSD in diabetic women, as well as erectile dysfunction in diabetic men.